Notícia dels projectes de creació inèdits de Sebastià Juan Arbó - Forcadell, Joan Antoni (Rassegna Iberistica)
Sebastià Juan Arbó was the author of a collection of previously unpublished literary and essayistic works. The inventory work carried out by Joan Antoni Forcadell on his personal archive at the Arxiu Comarcal del Montsià has brought to light the original manuscripts. This note presents an initial overview and emphasizes the need for an in-depth philological study. The materials, rich and varied, shed new light on the work of one of the most prominent authors of twentieth-century Catalan and Spanish literature.